Miasta w polityce spójności Unii Europejskiej - Borowiec, Jan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The position of the cities in the EU common policy is particular. In some sense, it reflects their role in the development of the regions. In the cities, especially in the metropolises significant part of regions production potential and their resources is concentrated. Cities experience also negative effects of concentration and urbanization. The creation of Union's cohesion must take into consideration special role of the cities in the development of the regions and processes of economic and social disintegration of urban areas. Cities benefit from structural actions and other development programs. Fulfilment of Lisbon Strategy obligations promoting competition and lasting economy based on knowledge brings the need of reorientation of cohesion policy priorities. It will strengthen a role of cities particular features in running the cohesion policy. Cities will also participate in a bigger degree in advantages of common actions important to global competitiveness of EU. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 13-26